Clinical impact of direct rotational atherectomy in patients with complex coronary artery lesions - Kyusup Lee; Ji-hoon Jung; Woojin Kwon; Dae-Won Kim; Mahn-Won Park; Ik Jun Choi; Jae-Hwan Lee; Yong Hoon Yoon; Jang Hoon Lee; Sang Rok Lee; Pil Hyung Lee; Seung-Whan Lee; et al. (Scientific Reports)
Abstract Owing to limited data on the optimal timing of rotational atherectomy (RA), we sought to evaluate the clinical impact of the early application of the RA strategy. Consecutive patients with severe coronary artery calcification were enrolled, who underwent percutaneous coronary intervention (PCI) using RA between January 2010 and October 2019 at 9 tertiary centers. Direct RA was defined as the early application of RA before the balloon was expanded to a size more than or equal to 2.0 mm. The primary endpoint was the composite outcome of technical failure or severe coronary dissection (type D, E, or F) during entire procedure. Of 581 lesions, 360 (62.0%) lesions underwent direct RA. The technical success rate was higher in the direct RA group than in the indirect RA group (97.5% vs. 93.7%, p = 0.021). The primary endpoint was more frequently observed in the indirect RA group than in the direct RA group (24.4% vs. 11.9%, p < 0.001). Multivariate logistic regression analysis revealed that the risk of the primary endpoint was higher in the indirect RA group than in the direct RA group (odds ratio 2.512, 95% CI 1.547–4.078, p < 0.001). Early application of RA may reduce the incidences of in-hospital adverse events and procedure-related complications.